Question and answer
add or subtract and simplify 6/x^2-7x+10+3/x-5
The answer for 6/x^2-7x+10+3/x-5 is 6/x^2-7 x+3/x+5.
Expert answered|jeifunk|Points 9233|
Question
Asked 3/25/2013 2:40:20 PM
0 Answers/Comments
Get an answer
New answers
Rating

There are no new answers.

Comments

There are no comments.

Add an answer or comment
Log in or sign up first.
Questions asked by the same visitor
find the LCD. 5/X-6, 7/X^2-12x+ 36
Weegy: Solution: 5/(x-6),7/(x^2-12x+36) - - - Factor the denominators: 5/(x-6),7/(x-6)^2 - - - - - - - - - - - - LCD = (x-6)^2 (More)
Question
Expert Answered
Asked 3/25/2013 2:27:12 PM
0 Answers/Comments
Add or substract and simplify your answers. 6/x^2 -7x + 10 + 3/x-5
Weegy: -7x = 56 x = 56/-7x x = -8 (More)
Question
Expert Answered
Asked 3/25/2013 2:53:02 PM
0 Answers/Comments
Solve the equation and check your solutions. if there is no solution, say so. 1/x +2/3x = 1/3
Weegy: ?6 + 3x = ?9 3x = -9 + 6 3x = -3 x = -1 User: Solve the equation and check your solutions. if there is no solution, say so. 5/4x+2=1/x Weegy: 4x=16 ===> x = 16/4 = 4 The solution is 4. User: Solve the equation and check your solutions. if there is no solution, say so. 9/2x+1=4/x (More)
Question
Not Answered
Updated 66 days ago|9/21/2014 1:13:20 AM
2 Answers/Comments
[Deleted]
Added 66 days ago|9/21/2014 1:02:06 AM
Deleted by janezeshun [9/21/2014 1:13:18 AM]
[Deleted]
Added 66 days ago|9/21/2014 1:07:07 AM
Deleted by janezeshun [9/21/2014 1:13:17 AM]
Multiply: 4x^3*2x^12
Weegy: 4x^3*2x^12 = 8x^15. User: . Divide: 6x^3/2x User: find: (x^5)^3 Weegy: (x^5)^3 = x^15 (More)
Question
Expert Answered
Updated 118 days ago|7/31/2014 4:06:28 PM
2 Answers/Comments
[Deleted]
Added 118 days ago|7/31/2014 4:05:26 PM
Unconfirmed by andrewpallarca [7/31/2014 4:06:20 PM], Deleted by andrewpallarca [7/31/2014 4:06:21 PM]
6x^3/2x = 3x^2
Added 118 days ago|7/31/2014 4:06:28 PM
This answer has been confirmed as correct, not copied, and helpful.
Multiply and Simplify: (x - 4)(x + 3)
Question
Updated 152 days ago|6/27/2014 10:37:51 AM
1 Answer/Comment
(x - 4)(x + 3)
=x^2+3x-4x-12
=x^2-x-12
Added 152 days ago|6/27/2014 10:37:50 AM
This answer has been confirmed as correct, not copied, and helpful.
18,451,769 questions answered
Popular Conversations
Simplify 12A + 2 + A - 1. 14A - 1 13A - 1 13A + 1 User: ...
Weegy: 12(A - B) = 12A - 12B User: Simplify 10x - 3x + (-5x). -2x 2x 18x -18x Weegy: c.18x User: Simplify ...
11/25/2014 3:05:18 PM| 6 Answers
True or false carbohydrates are made up of carton, hydrogen, and ...
Weegy: The answer is True. Here is the source link: User: The two main types of fiber are?
11/25/2014 7:45:43 PM| 5 Answers
x + y = k x - y = k
Weegy: 8 1/3 - 1 5/6 = 25/3 - 11/6; = 50/6 - 11/6; = 39/6; = 13/2; = 6 1/2 User: 5x + y = 6 5x + 3y = -4 Weegy: ...
11/25/2014 9:09:05 AM| 4 Answers
Determine the solution set of (2x - 5)2 = 11.
Weegy: 2x - 3 = 9 2x = 9 + 3 2x = 12 x = 12/2 x = 6 User: Determine the solution set of (3x + 1)2 - 100 = ...
11/25/2014 11:37:07 AM| 4 Answers
The first English child born in the new world
Weegy: TRUE The first English child born in the new world
11/25/2014 1:29:56 PM| 4 Answers
20,000 pounds equals how many English tons?
11/25/2014 3:30:36 AM| 3 Answers
Simplify 20 + (2 + r). r + 22 22r 20r
Weegy: r + 22 User: Simplify (5a)(5b). 10ab 25ab 55ab Weegy: (5a)(5b) = 25ab User: Simplify 7.95 - 3.86 + ...
11/25/2014 8:53:09 AM| 3 Answers
Which personal pronoun best completes the sentence? How is it used? ...
Weegy: My father made my sister and ME blueberry pancakes for breakfast. The correct pronoun is: me; indirect object. ...
11/25/2014 9:42:28 AM| 3 Answers
t Object]User: y + 3 = 2x y + 4 = 3x If you use the comparison ...
Weegy: 31/8 and 25/8 User: What is the result of adding the system of equations? 2x + y = 4 3x - y = 6 x = 2 x = ...
11/25/2014 10:32:36 AM| 3 Answers
Which of the following is the correct factored form of the given ...
Weegy: The correct factored form of the given equation x^2 + 3x - 4 = 0 is (x - 1)(x + 4) = 0. User: olve n3 + 2n2 ...
11/25/2014 11:30:00 AM| 3 Answers
Which of the following is the correct factored form of the given ...
Weegy: (x - 3)^2 = 0 written in general form is: x^2 - 6x + 9 = 0 Expand (x - 3)^2 = x^2 - 3x - 3x + 9 = x^2 - 6x + ...
11/25/2014 11:33:47 AM| 3 Answers
Weegy Stuff
S
L
1
L
P
C
1
P
C
1
L
P
C
1
Points 2660 [Total 14370]| Ratings 10| Comments 2560| Invitations 0|Offline
S
L
Points 1455 [Total 3741]| Ratings 0| Comments 1455| Invitations 0|Offline
S
L
Points 777 [Total 1298]| Ratings 6| Comments 717| Invitations 0|Offline
S
1
L
1
L
P
P
L
P
Points 764 [Total 14138]| Ratings 0| Comments 764| Invitations 0|Offline
S
Points 735 [Total 767]| Ratings 1| Comments 725| Invitations 0|Offline
S
1
L
L
Points 273 [Total 6667]| Ratings 0| Comments 273| Invitations 0|Offline
S
L
Points 161 [Total 1457]| Ratings 3| Comments 131| Invitations 0|Offline
S
Points 86 [Total 86]| Ratings 1| Comments 76| Invitations 0|Offline
S
Points 50 [Total 50]| Ratings 0| Comments 0| Invitations 5|Offline
S
Points 46 [Total 46]| Ratings 3| Comments 6| Invitations 1|Offline
Home | Contact | Blog | About | Terms | Privacy | Social | ©2014 Purple Inc.